If\[{I_n} = \int {{{\cot }^n}xdx} \], then \[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}}\]equals to: (where\[u = \cot x\]).
A.\[u + \dfrac{{{u^2}}}{2} + ....... + \dfrac{{{u^9}}}{9}\]
B.\[ - \left( {u + \dfrac{{{u^2}}}{2} + ....... + \dfrac{{{u^9}}}{9}} \right)\]
C.\[ - \left( {u + \dfrac{{{u^2}}}{{2!}} + ....... + \dfrac{{{u^9}}}{{9!}}} \right)\]
D.\[\dfrac{u}{2} + \dfrac{{2{u^2}}}{3} + ....... + \dfrac{{9{u^2}}}{{10}}\]
Answer
Verified
482.1k+ views
Hint: Use integration reduction method which relies on recurrence relations. This method is used when the expression contains integer parameters in the form of power of elementary functions. This method can be derived from any common method of integration, like partial integration or integration by substitution.
Complete step by step solution:
In this question write \[{I_n} = \int {{{\cot }^n}xdx} \]in the reduction form and then use the chain rule to simplify and find the value of\[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}}\].
Given \[{I_n} = \int {{{\cot }^n}xdx} \] the use the reduction method, we can write
\[{I_n} = \int {{{\cot }^n}xdx} = \int {{{\cot }^{n - 2}}{{\cot }^2}xdx} \]
We know\[\cos e{c^2}x = 1 + {\cot ^2}x\], hence we can write
\[
{I_n} = \int {{{\cot }^{n - 2}}x\left( {\cos e{c^2}x - 1} \right)dx} \\
{I_n} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx - \int {{{\cot }^{n - 2}}x} dx} \\
\]
Since\[{I_n} = \int {{{\cot }^n}xdx} \]hence we can write \[\int {{{\cot }^{n - 2}}xdx = {I_{n - 2}}} \]
So we can write:
\[
{I_n} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx - {I_{n - 2}}} \\
{I_n} + {I_{n - 2}} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx} \\
\]
Now let us assume \[\cot x = t\]
By differentiating \[\cot x = t\] with respect to t we get,
\[
\dfrac{d}{{dx}}(\cot x) = \dfrac{{dt}}{{dx}} \\
- \cos e{c^2}xdx = dt \\
\]
Hence we can write:
\[
{I_n} + {I_{n - 2}} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx} \\
= - \int {{t^{n - 2}}dt} \\
\]
Now integrate:
\[
{I_n} + {I_{n - 2}} = - \int {{t^{n - 2}}dt} \\
= - \dfrac{{{t^{n - 2 + 1}}}}{{n - 2 + 1}} = - \dfrac{{{t^{n - 1}}}}{{n - 1}} = - \dfrac{{{{\cot }^{n - 1}}x}}{{n - 1}} \\
\]
Hence,
\[{I_n} + {I_{n - 2}} = - \dfrac{{{{\cot }^{n - 1}}x}}{{n - 1}}\] where, \[n \geqslant 2\]
Now replace n with (n+2), we can write
\[{I_{n + 2}} + {I_n} = - \dfrac{{{{\cot }^{n + 1}}x}}{{n + 1}}\]
Now we have to find the value of\[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}}\], write the given function in the pair of the common difference of 2 as \[{I_{n + 2}},{I_n}\]:
\[
{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}} = \left( {{I_0} + {I_2}} \right) + \left( {{I_1} + {I_3}} \right) + \left( {{I_2} + {I_4}} \right) + \left( {{I_3} + {I_5}} \right) + \left( {{I_4} + {I_6}} \right) + \left( {{I_5} + {I_7}} \right) + \left( {{I_8} + {I_{10}}} \right) + \left( {{I_7} + {I_9}} \right) \\
= - \cot x - \dfrac{{{{\cot }^2}x}}{2} - \dfrac{{{{\cot }^3}x}}{3} - .......... - \dfrac{{{{\cot }^9}x}}{9} \\
= - \left( {\cot x + \dfrac{{{{\cot }^2}x}}{2} + \dfrac{{{{\cot }^3}x}}{3} + .......... + \dfrac{{{{\cot }^9}x}}{9}} \right) \\
\]
Since \[u = \cot x\]is given hence, we can write
\[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}} = - \left( {u + \dfrac{{{u^2}}}{2} + \dfrac{{{u^3}}}{3} + .......... + \dfrac{{{u^9}}}{9}} \right)\]
Hence option B is correct.
Note: While substituting the real parameter of the question with the auxiliary parameter, one should be sure that it will not make the problem more complex. However, selecting an auxiliary parameter completely depends on the individual point of view.
Complete step by step solution:
In this question write \[{I_n} = \int {{{\cot }^n}xdx} \]in the reduction form and then use the chain rule to simplify and find the value of\[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}}\].
Given \[{I_n} = \int {{{\cot }^n}xdx} \] the use the reduction method, we can write
\[{I_n} = \int {{{\cot }^n}xdx} = \int {{{\cot }^{n - 2}}{{\cot }^2}xdx} \]
We know\[\cos e{c^2}x = 1 + {\cot ^2}x\], hence we can write
\[
{I_n} = \int {{{\cot }^{n - 2}}x\left( {\cos e{c^2}x - 1} \right)dx} \\
{I_n} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx - \int {{{\cot }^{n - 2}}x} dx} \\
\]
Since\[{I_n} = \int {{{\cot }^n}xdx} \]hence we can write \[\int {{{\cot }^{n - 2}}xdx = {I_{n - 2}}} \]
So we can write:
\[
{I_n} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx - {I_{n - 2}}} \\
{I_n} + {I_{n - 2}} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx} \\
\]
Now let us assume \[\cot x = t\]
By differentiating \[\cot x = t\] with respect to t we get,
\[
\dfrac{d}{{dx}}(\cot x) = \dfrac{{dt}}{{dx}} \\
- \cos e{c^2}xdx = dt \\
\]
Hence we can write:
\[
{I_n} + {I_{n - 2}} = \int {{{\cot }^{n - 2}}x\cos e{c^2}xdx} \\
= - \int {{t^{n - 2}}dt} \\
\]
Now integrate:
\[
{I_n} + {I_{n - 2}} = - \int {{t^{n - 2}}dt} \\
= - \dfrac{{{t^{n - 2 + 1}}}}{{n - 2 + 1}} = - \dfrac{{{t^{n - 1}}}}{{n - 1}} = - \dfrac{{{{\cot }^{n - 1}}x}}{{n - 1}} \\
\]
Hence,
\[{I_n} + {I_{n - 2}} = - \dfrac{{{{\cot }^{n - 1}}x}}{{n - 1}}\] where, \[n \geqslant 2\]
Now replace n with (n+2), we can write
\[{I_{n + 2}} + {I_n} = - \dfrac{{{{\cot }^{n + 1}}x}}{{n + 1}}\]
Now we have to find the value of\[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}}\], write the given function in the pair of the common difference of 2 as \[{I_{n + 2}},{I_n}\]:
\[
{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}} = \left( {{I_0} + {I_2}} \right) + \left( {{I_1} + {I_3}} \right) + \left( {{I_2} + {I_4}} \right) + \left( {{I_3} + {I_5}} \right) + \left( {{I_4} + {I_6}} \right) + \left( {{I_5} + {I_7}} \right) + \left( {{I_8} + {I_{10}}} \right) + \left( {{I_7} + {I_9}} \right) \\
= - \cot x - \dfrac{{{{\cot }^2}x}}{2} - \dfrac{{{{\cot }^3}x}}{3} - .......... - \dfrac{{{{\cot }^9}x}}{9} \\
= - \left( {\cot x + \dfrac{{{{\cot }^2}x}}{2} + \dfrac{{{{\cot }^3}x}}{3} + .......... + \dfrac{{{{\cot }^9}x}}{9}} \right) \\
\]
Since \[u = \cot x\]is given hence, we can write
\[{I_0} + {I_1} + 2\left( {{I_2} + {I_3} + ...... + {I_8}} \right) + {I_9} + {I_{10}} = - \left( {u + \dfrac{{{u^2}}}{2} + \dfrac{{{u^3}}}{3} + .......... + \dfrac{{{u^9}}}{9}} \right)\]
Hence option B is correct.
Note: While substituting the real parameter of the question with the auxiliary parameter, one should be sure that it will not make the problem more complex. However, selecting an auxiliary parameter completely depends on the individual point of view.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Draw a labelled sketch of the human eye class 12 physics CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
What are the major means of transport Explain each class 12 social science CBSE